2007
DOI: 10.1086/511859
|View full text |Cite
|
Sign up to set email alerts
|

Zoonoses in Solid-Organ and Hematopoietic Stem Cell Transplant Recipients

Abstract: Numerous reports exist of the transmission of zoonoses to humans during and after solid-organ and hematopoietic stem cell transplantation. Donor-derived infections of numerous etiologies, including West Nile virus infection, Chagas disease, toxoplasmosis, rabies, lymphocytic choriomeningitis virus infection, and infection due to Brucella species have been reported. Most zoonoses occur as a primary infection after transplantation, and immunocompromised patients are more likely to experience significant morbidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
105
0
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(117 citation statements)
references
References 158 publications
0
105
0
8
Order By: Relevance
“…Éstas pueden ser resultado de una infección primaria adquirida, por exposición posttrasplante o por reactivación de una infección latente 19 . La estrongiloidiasis en pacientes que recibieron un trasplante tiene importancia debido a que el tratamiento inmunosupresor genera que sean más susceptibles a desarrollar la infección o sus formas graves en pacientes ya infectados, como por ejemplo, síndrome de hiperinfección (presencia de gran cantidad de parásitos en un mismo órgano, en general intestino) y la forma diseminada (afectación de múltiples órganos) 20 .…”
Section: Estrongiloidiasis Y Trasplantesunclassified
“…Éstas pueden ser resultado de una infección primaria adquirida, por exposición posttrasplante o por reactivación de una infección latente 19 . La estrongiloidiasis en pacientes que recibieron un trasplante tiene importancia debido a que el tratamiento inmunosupresor genera que sean más susceptibles a desarrollar la infección o sus formas graves en pacientes ya infectados, como por ejemplo, síndrome de hiperinfección (presencia de gran cantidad de parásitos en un mismo órgano, en general intestino) y la forma diseminada (afectación de múltiples órganos) 20 .…”
Section: Estrongiloidiasis Y Trasplantesunclassified
“…The approach to screening of organ donors varies according to the: (1) national and regional regulations, (2) availability of certain microbiological assays or tests in the transplantation center, and (3) epidemiology of infections in the region, particularly endemic infections such as brucellosis [113]. The infections that can be transmitted by SOT are included in Table 1, [104,105,[114][115][116][117].…”
Section: Donor-derived Infectionsmentioning
confidence: 99%
“…Infectious pathogens may be carried by the graft or by transfusion of blood products during or after transplantation [117]. Transmission of tropical infectious diseases occurs through 3 main routes: (1) donor-derived infections, (2) reactivation of old or latent infections such as tuberculosis or brucellosis, or (3) de novo transmission occurring during the post-transplant period.…”
Section: Post-transplant Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Concerning the risk of bacteremias owing to enteric infection, solid organ transplant recipients have higher rates ranging as high as 70% compared with 3-4% in normal hosts and a higher rate of metastatic focus of infection. 6 A recommended periodic assessment of CD4 cell counts or immunoglobulin levels every 3-4 months after transplantation is recommended by some authors. 7 Large-scale retrospective studies have confirmed that the risk of secondary cancers is 3-13 times as high among patients who underwent SCT as among the age-matched control population.…”
mentioning
confidence: 99%